Liquidity creation and competition in the banking industry pre and post Arab Spring in Mena region - Abraheem, Nagea; Yahya, M. H.; Muhammad, Junaina; Ab Razak, Nazrul Hisyam (Allied Business Academies, 2020)
Competition is one of the determinants that influences banks’ liquidity creation. Political transitions in the MENA region have affected many aspects of the region, including its economy. The banking sector, being a crucial element in the financial system, is also affected. This study aims to examine the impact of ‘competition’, ‘political risk’ and ‘stability of banking industry’ on liquidity creation, vis-a-vis political transition (i.e. Arab Spring). The ‘availability of deposit insurance system’, bank ‘type’ and ‘size’ are used as control variables in this study. The sample in this study includes 55 banks from the MENA region (i.e. Arab Saudi, Bahrain, Egypt, Jordan, Kuwait, Lebanon, and Tunisia), for the period between 2006 and 2015. This study finds that liquidity creation is negatively related to competition in the period before political transition and positively related in the period after political transition. Moreover, political risk positively influences liquidity creation for both pre and post political transition periods. However, the ‘stability of the banking industry’ and the ‘availability of deposit insurance system’ reduce liquidity creation in both periods.